IS THERE ANY DIFFERENCE IN RA PATIENTS FOR METHOTREXATE USE VS. LEFLUNOMIDE USE AS A CONCOMITANT TREATMENT WITH BIOLOGICAL AND TARGETED SYNTHETIC DMARDS IN TURKBIO REGISTRY? - Inanc, N.; Ozen, G.; Yalcinkaya, Y.; Dalkilic, E.; Koca, S. S.; Can, G.; Onen, F. (Bmj Publishing Group, 2018)
[Abstract Not Available]
Congress of the European-League-Against-Rheumatism (EULAR) -- JUN 13-16, 2018 -- Amsterdam, NETHERLANDS